A collection of enhancer trap insertional mutants for functional genomics in tomato. Issue 11 (20th April 2017) - Pérez‐Martín, Fernando; Yuste‐Lisbona, Fernando J.; Pineda, Benito; Angarita‐Díaz, María Pilar; García‐Sogo, Begoña; Antón, Teresa; Sánchez, Sibilla; Giménez, Estela; Atarés, Alejandro; Fernández‐Lozano, Antonia; Ortíz‐Atienza, Ana; García‐Alcázar, Manuel; et al.
Summary: With the completion of genome sequencing projects, the next challenge is to close the gap between gene annotation and gene functional assignment. Genomic tools to identify gene functions are based on the analysis of phenotypic variations between a wild type and its mutant; hence, mutant collections are a valuable resource. In this sense, T‐DNA collections allow for an easy and straightforward identification of the tagged gene, serving as the basis of both forward and reverse genetic strategies. This study reports on the phenotypic and molecular characterization of an enhancer trap T‐DNA collection in tomato ( Solanum lycopersicum L.), which has been produced by Agrobacterium ‐mediated transformation using a binary vector bearing a minimal promoter fused to the uidA reporter gene. Two genes have been isolated from different T‐DNA mutants, one of these genes codes for a UTP‐glucose‐1‐phosphate uridylyltransferase involved in programmed cell death and leaf development, which means a novel gene function reported in tomato. Together, our results support that enhancer trapping is a powerful tool to identify novel genes and regulatory elements in tomato and that this T‐DNA mutant collection represents a highly valuable resource for functional analyses in this fleshy‐fruited model species.